Analysis of Gene Effects Controlling Yield Contributing Traits in Grass pea (Lathyrus sativus L.) - R, Gonmei; M. S, Jeberson; Kumar, Manish; N. B., Singh; K. S., Shashidhar; Sharma, Ph. Ranjit (International Journal of Bio-resource and Stress Management, 2018)
The seven parents and their 21 F1s were grown in randomized block design with 3 replications during rabi 2015-16. In the field experiment, observations on 12 quantitative characters were recorded for genetic analysis. The analysis of variance for combining ability revealed significant differences among crosses for all the characters studied except for days to first flowering. In case of general combining ability effects, RLS 3004-5 and Pusa 24 were identified as the most promising parents for involving in hybridization programme. On the basis of specific combining ability effects, five crosses exhibited highly significant SCA effects for seed yield plant-1 with two to six other yield components. Among cross combinations, Prateek×RLS 3009-2, DLY 13-7×Pusa 24, DLY 13-7×RLS 3004-5 and RLS 3004-5×Bio L 212 were identified as the most promising crosses for improvement of seed yield per plant and three to six of its component traits. The manifestation of heterosis for seed yield was evidenced by superiority of hybrids over better parent and over standard check variety (Bio L 212). Out of 21 cross combinations, 5 crosses exhibited significant heterosis over their better parent as well as standard check. Overall on the basis of results of mean performance, including GCA and SCA effects and standard heterosis, Prateek×RLS 3009-2, DLY 13-7×Pusa 24 and DLY 13-7×RLS 3004-5 were identified as the most promising cross combinations for improvement of seed yield in grasspea.